2022
DOI: 10.1021/jacs.2c09474
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Controlled Energy Transfer Quenching of Fluorophore-Labeled DNA SAMs Enables In Situ Study of These Complex Electrochemical Interfaces

Abstract: Interfaces modified by a molecular monolayer can be challenging to study, particularly in situ, requiring novel approaches. Coupling electrochemical and optical approaches can be useful when signals are correlated. Here we detail a methodology that uses redox electrochemistry to control surface-based fluorescence intensity for detecting DNA hybridization and studying the uniformity of the surface response. A mixed composition single-strand DNA SAM was prepared using potential-assisted thiol exchange with two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In situ AFM studies of DNA SAMs provide a single molecule view into the DNA local environment, but these can be challenging measurements that require specialized equipment. ,, Optical methods like fluorescence microscopy have also been reported, providing a more detailed picture of the surface and revealing underlying problems, such as defects and nonspecific DNA assembly, forming aggregates and clusters. ,, In addition, we have used this methodology coupled with electrochemical control of the interfacial potential to interrogate the characteristics and dynamics of the DNA SAM when prepared under a variety of conditions. While these fluorescence imaging methods are reliable and provide spatially specific information, they are still limited to providing the average behavior on micrometer or larger regions. Coupling electrochemical control over the interfacial potential with fluorescence imaging, we have shown that using potential modulated fluorescence intensity can provide some information on the average distance between tethered DNA probes. , However, these rely on the steric limitation of DNA reorientation upon the application of negative or positive potentials and are indirectly dependent on the distance between tethered DNA.…”
Section: Introductionmentioning
confidence: 99%
“…In situ AFM studies of DNA SAMs provide a single molecule view into the DNA local environment, but these can be challenging measurements that require specialized equipment. ,, Optical methods like fluorescence microscopy have also been reported, providing a more detailed picture of the surface and revealing underlying problems, such as defects and nonspecific DNA assembly, forming aggregates and clusters. ,, In addition, we have used this methodology coupled with electrochemical control of the interfacial potential to interrogate the characteristics and dynamics of the DNA SAM when prepared under a variety of conditions. While these fluorescence imaging methods are reliable and provide spatially specific information, they are still limited to providing the average behavior on micrometer or larger regions. Coupling electrochemical control over the interfacial potential with fluorescence imaging, we have shown that using potential modulated fluorescence intensity can provide some information on the average distance between tethered DNA probes. , However, these rely on the steric limitation of DNA reorientation upon the application of negative or positive potentials and are indirectly dependent on the distance between tethered DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The coupling between electrochemistry and fluorescence microscopy allows monitoring in a non‐invasive, synchronous and very sensitive way, the electrochemical and the fluorescence signals arising ultimately from single molecules located at the proximity of the electrode. [ 21,22 ] It is worth noting that the electrofluochromism of a single layer, [ 23 ] and of isolated non‐dyad molecules, [ 24 ] have been recently reported, demonstrating the feasibility of such sensitive detection.…”
Section: Introductionmentioning
confidence: 99%
“…9 Even more recently, Bizzotto and colleagues developed a FRET-based technique that monitors the binding of a target DNA sequence to the recognition strands. 10 Together, studies such as these are really starting to teach us how these interfaces at the molecular level, finally! The tools are starting to come to solve the conundrum of us being able to design sensing interfaces at the molecular level yet not be able to characterize them.…”
mentioning
confidence: 99%
“…Going back to the DNA interfaces, using such techniques Schwartz and colleagues have shown how a solution-based species searches the surface for the DNA recognition species; Bizzotto and co-workers have shown how the DNA distributes across the surface, forming clumps, rather than being evenly distributed; while Harris, Heemstra, and colleagues have shown how DNA aptamers structurally switch on surfaces . Even more recently, Bizzotto and colleagues developed a FRET-based technique that monitors the binding of a target DNA sequence to the recognition strands . Together, studies such as these are really starting to teach us how these interfaces work at the molecular level, finally!…”
mentioning
confidence: 99%